Comparative efficacy between surgical intervention, organophosphorus and ivermectin against humpsore (Stephanofilariasis) in cattle - M.Z.U. Ibrahim; M.A. Hashim; M.A.Hossain; Imad Ibrahim Ali Al-Sultan (Design for Scientific Renaissance, 2013)
The experiment was carried out in 40 cattle to investigate the comparative efficacy of surgical intervention, using organophosphorus (Neguvon R ) and ivermectin against skin lesions due to Stephanofilariasis. Cattle of 1.5 to 6 years of age irrespective of sex having diagnosed skin lesions (Stephanofilariasis) were used in this experiment. Selected cattle were divided into four equal groups (group A, B, C and D): each group consisted of 10 cattle. Group A was treated by surgical excision of affected skin lesion. Animals of group B was treated with organophosphorus, Trichlorophon (Neguvon R Sapco, Unichem, Bangladesh) ointment applied topically. Group C treated with Ivermectin (A-mectin, The ACME Lab. Ltd, Bangladesh) was administered subcutaneously @ 0.2 mg/kg body weight and repeated after 21 days at same dose. Group D kept as control Group. Cattle treated surgically were completely cured within 15-20 days in all cases. The rate of healing of lesions was rapid compare to organophosphorus and ivermectin treated groups and success of healing was 100%, whereas animals treated with organophosphorus ointment cured partially after 45 days of treatment and success of healing was 60% and those treated with ivermectin also cured partially in 45 days of treatment and the success of healing was 70%. Surgical excision was more effective in comparison to other treatments in respect to time required for healing, presence of exudates, alopecia and recurrence of infection which was shown by histopathologically as the restoration of surrounding hair follicle and increased production of new capillaries around the scar tissue at the newly cured area. Also, it was evident that the treatment with ivermectin was more effective than organophosphorus application in success of healing. It is suggested that surgical excision of the lesions produced by Stephanofilariasis may be used as an alternative treatment method in cattle.